Clinical application of unilateral biportal endoscopic lumbar interbody fusion in lumbar degenerative diseases: a multi-center study - Chen, Yunsheng; Wu, Jian; Li, Qiaoxin; Wu, Yaohong; Xu, Canhua; Chen, Rongchun; Shi, Jiangyou; Liu, Liping; Sun, Linbo; Xiong, Jun (Frontiers in Neurology, 2025)
ObjectiveThis study endeavors to evaluate the clinical efficacy of unilateral biportal endoscopic lumbar interbody fusion (ULIF) in managing lumbar degenerative diseases (LDD) through a multi-center investigation.MethodsOne hundred patients diagnosed with LDD between August 2022 and August 2024 were enrolled and allocated to either the ULIF cohort (ULIF group, n = 50) or the conventional open posterior lumbar interbody fusion (PLIF) cohort (PLIF group, n = 50). Surgical metrics (operative time, intraoperative blood loss, postoperative drainage volume, and hospital duration) alongside the three-month interbody fusion rate were compared. Preoperative and postoperative pain Visual Analogue Scale (VAS) scores, serum inflammatory cytokine profiles (TNF-α, IL-6, IL-4), Japanese Orthopaedic Association (JOA) scores, and Oswestry Disability Index (ODI) scores were analyzed. Postoperative complications were documented.ResultsThe ULIF group demonstrated a higher three-month interbody fusion rate than the PLIF group (P < 0.05). Additionally, the ULIF cohort exhibited shorter operative times, diminished intraoperative blood loss, reduced postoperative drainage, and abbreviated hospital stays compared with the PLIF group (P < 0.05). Seven-day postoperative VAS scores were lower in the ULIF group relative to the PLIF group (P < 0.05). TNF-α and IL-6 levels were lower, while IL-4 was elevated in the ULIF cohort at 7 days postoperatively relative to the PLIF group (P < 0.05). JOA scores were superior and ODI scores were lower in the ULIF group at 7 days and 3 months postoperatively versus the PLIF group (P < 0.05). No significant difference in overall postoperative complication rates was observed between groups (P > 0.05).ConclusionULIF enhances postoperative pain relief, functional recovery, and inflammatory resolution, while simultaneously shortening operative and hospitalization durations, minimizing intraoperative blood loss, and maintaining a favorable safety profile in LDD patients.